Assessment of knowledge and implementation practices of the ventilator acquired pneumonia (VAP) bundle in the intensive care unit of a private hospital - Cybele Lara Abad (BMC, 2021)
Abstract Studies have shown that a ventilator associated pneumonia (VAP) bundle significantly decreases VAP rates. In this study, we evaluated existing knowledge, practices, and adherence of nurses and infection control preventionists (ICP) to the VAP bundles of care in the intensive care unit (ICU) by using qualitative and quantitative tools. Of 60 participants (56 nurses and 4 ICPs), mean knowledge score regarding specific evidence-based VAP guidelines was 5 (range 3–8) out of 10 points. Self-reported adherence to the VAP bundle ranged from 38.5 to 100%, with perfect compliance to head of bed elevation, and poorest compliance with readiness to extubate. Overall VAP median bundle compliance was 84.6%. Knowledge regarding specific components of VAP prevention is lacking. Formal training and interactive educational sessions should be performed regularly to assess the competency of key personnel regarding the VAP bundle, especially in the context of rapid nurse turnover. Incentives for retention of nurses should also be considered, so that knowledge of hospital specific initiatives such as the VAP bundles of care can be cultivated over time.